2016
DOI: 10.1017/s1478951516000584
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care for terminally ill patients in the intensive care unit: Systematic review and metaanalysis

Abstract: Introduction of palliative care teams can reduce mortality rates in the ICU, and perhaps shorten length of stay in the ICU for terminally ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 28 publications
1
26
2
3
Order By: Relevance
“…( 1 ) Because hospitals are a major site for end-of-life care, ( 2 - 4 ) interventions to improve PC during terminal hospitalizations have been implemented and analyzed in the literature. ( 13 - 15 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 1 ) Because hospitals are a major site for end-of-life care, ( 2 - 4 ) interventions to improve PC during terminal hospitalizations have been implemented and analyzed in the literature. ( 13 - 15 )…”
Section: Discussionmentioning
confidence: 99%
“…There is great variability in decisions of prognostication and the limitations of medical treatment, ( 5 , 12 ) and it has been suggested that palliative care (PC) interventions can modify decisions about care goals and patient allocation. ( 13 - 15 ) For instance, advanced care planning or PC referral in the wards or during an ICU stay may reduce inappropriate ICU admissions. ( 14 ) It has been proposed that one of the main drivers of this change is timely and sensitive communication about appropriate goals of care, taking into consideration the patient's condition, prognosis and values.…”
Section: Introductionmentioning
confidence: 99%
“…Interdisciplinary team care Adults or mixed samples ICU Patient outcome: mortality 2 SRs 24,30 Two reviews came to different conclusions: one review found that ICU-based palliative care team interventions did not change hospital mortality; however, another review found that the introduction of palliative care teams can reduce mortality rates in the ICU.…”
Section: (Im In)mentioning
confidence: 99%
“…There was very low-quality evidence from two reviews of a positive impact of interdisciplinary team care in the ICU on mortality and family satisfaction with care, due to an absence of randomized controlled trials studying these outcomes, inconsistency in conclusions, and lack of pooled effect estimates. 24,30 Telehealth: There was moderate-quality evidence on a positive impact of telehealth for adults and children in the home/outpatient setting on psychological health (i.e., improvements in anxiety, depression, distress, PTSD; however, no effect estimates were provided), 39,44,46,47 but low-to very low-quality evidence for all other outcomes including resource use, patient quality of life, physical symptoms, satisfaction with care, and family/caregiver quality of life, due to inconsistent findings, lack of pooled effect estimates, and study limitations described in included reviews.…”
Section: (Im In)mentioning
confidence: 99%
“…38 Similar findings have also been reported with opioids used for dyspnea relief 60 and palliative drug therapy for terminally ill patients in the intensive care unit. 61 The effect has been attributed to the relief from distress. 60…”
Section: Adverse Effects and Survivalmentioning
confidence: 99%